2019
DOI: 10.1007/s00280-019-03952-w
|View full text |Cite
|
Sign up to set email alerts
|

A prospective phase I multicentre randomized cross-over pharmacokinetic study to determine the effect of food on abiraterone pharmacokinetics

Abstract: PurposeAbiraterone acetate is used at a fixed oral dose of 1000 mg once daily (OD) taken fasted. By administering abiraterone acetate with food, a reduced dose can potentially be given while maintaining equivalent abiraterone exposure. Moreover, administering abiraterone acetate with a breakfast is considered more patient friendly. The aim of this study was to establish the bio-equivalent lower dose of abiraterone when taken with a continental breakfast (CB) compared to the standard intake of 1000 mg OD fasted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Niraparib exposure, when used in combination with AAP, was dose proportional, as reported previously for niraparib monotherapy; the time to maximum concentration was also similar (approximately 3–4 h) [ 29 ]. The abiraterone pharmacokinetics for the combination were also comparable to abiraterone 1000 mg monotherapy data [ 34 ].…”
Section: Discussionmentioning
confidence: 81%
“…Niraparib exposure, when used in combination with AAP, was dose proportional, as reported previously for niraparib monotherapy; the time to maximum concentration was also similar (approximately 3–4 h) [ 29 ]. The abiraterone pharmacokinetics for the combination were also comparable to abiraterone 1000 mg monotherapy data [ 34 ].…”
Section: Discussionmentioning
confidence: 81%
“…This reduced dose was included as an alternative recommendation in the NCCN clinical practice guidelines for prostate cancer [17]. However, there is still debate over the bioavailability and benefits of low-dose versus standard regimens [34][35][36]. Assuming that efficacy is similar, widespread use of a low-dose abiraterone regimen would result in dramatic cost savings and greater population coverage of this treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This reduced dose was included as an alternative recommendation in the NCCN clinical practice guidelines for prostate cancer [17]. However, there is still debate over the bioavailability and benefits of low-dose versus standard regimens [34][35][36]. Assuming that Step-by-step cost-saving analysis (in U.S.…”
Section: Discussionmentioning
confidence: 99%
“…The online version of this article (https://doi.org/10.1208/s12248-020-00505-5) contains supplementary material, which is available to authorized users. (3). This implies a need for the development of novel formulation strategies that would allow food effect elimination and thus safe dosing regimen for abiraterone acetate.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…An example of such a hard-to-formulate drug is abiraterone acetate, a prodrug of androgen biosynthesis inhibitor abiraterone, marketed under the original brand name Zytiga ® and used as a medication for the treatment of metastatic castration-resistant prostate cancer (2). Abiraterone acetate has an extremely low bioavailability in the fasted state (estimated to be less than 10%) and exhibits a highly variable increase in bioavailability in the fed state (3)(4)(5). It has been reported that intake with high-fat meal leads to increase in overall exposures by approximately 17-and 10fold, in terms C max and AUC, respectively.…”
Section: Introductionmentioning
confidence: 99%